Towards in-vivo grown bioelectronics: utilising bipolar electrochemistry - Robinson, Andie Jane (2022)
Bipolar electrochemistry brings exciting possibilities to be able to grow electronics in situ within biological systems, thus creating electronics that seamlessly merge with biology and are on a similar scale to cellular components. This could allow the development of novel applications to tackle some of the world’s greatest health burdens, such as cancer. Therefore, the aim of this thesis is to develop bioelectronic systems, utilising bipolar electrochemistry, for possible applications in cancer treatment.